Rationale and design of the violence, injury and trauma observatory (VITO): the Cape Town VITO pilot studies protocol. Issue 12 (22nd December 2017) - Jabar, Ardil; Oni, Tolu; Engel, Mark E; Cvetkovic, Nemanja; Matzopoulos, Richard
Abstract : The establishment of violence and injury observatories elsewhere has been found to reduce the burden within a relatively short period. Currently no integrated system exists in South Africa to provide collated data on violence, to allow for targeted interventions and routine monitoring and evaluation.This research seeks to identify if bringing multiple data sources, including but not limited to data from the South African Police Service (SAPS), Forensic Pathology Services (FPS), Emergency Medical Services (EMS) and local hospital clinical databases, together are (1) feasible; (2) able to generate data for action, that is valid, reliable and robust and (3) able to lead to interventions. The violence, injury and trauma observatory (VITO) is a planned collaborative, multicentre study of clinical, police and forensic data for violence and injury in the City of Cape Town, where a local context exists of access to multiple source of health and non-health data. The VITO will initially be piloted in Khayelitsha, a periurban community characterised by increased rates of violence, where fatal and non-fatal injury data will be sourced from within the community for the period 2012–2015 and subjected to descriptive statistics and time-trend analyses. Analysed data will be visualised using story maps, data clocks, web maps and other geographical information systems-related products. This study has been approved by the University of Cape Town's Human Research Ethics Committee (HREC 861/2016). We intend to disseminate our findings among stakeholders within the local government safety cluster, non-governmental organisations working within the violence prevention sector and the afflicted communities through the SAPS and violence prevention through urban upgrading community forums. Findings from this work will serve to identify important issues and trends, influence public policy and develop evidence-based interventions.